If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -13(n + 20) = (-11n + 38) Reorder the terms: -13(20 + n) = (-11n + 38) (20 * -13 + n * -13) = (-11n + 38) (-260 + -13n) = (-11n + 38) Reorder the terms: -260 + -13n = (38 + -11n) Remove parenthesis around (38 + -11n) -260 + -13n = 38 + -11n Solving -260 + -13n = 38 + -11n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '11n' to each side of the equation. -260 + -13n + 11n = 38 + -11n + 11n Combine like terms: -13n + 11n = -2n -260 + -2n = 38 + -11n + 11n Combine like terms: -11n + 11n = 0 -260 + -2n = 38 + 0 -260 + -2n = 38 Add '260' to each side of the equation. -260 + 260 + -2n = 38 + 260 Combine like terms: -260 + 260 = 0 0 + -2n = 38 + 260 -2n = 38 + 260 Combine like terms: 38 + 260 = 298 -2n = 298 Divide each side by '-2'. n = -149 Simplifying n = -149
| 0=9x^2-2kx+3k | | 9-x*1/2=13 | | 24=2/3V | | 5/12/360 | | -2x-3y=-30 | | 2.25+3.50x=44.25 | | 360/6x | | 2(10x-5)=4(5x+2) | | 14p+20q+p-7q-3p= | | 44.25=2.25+3.50x | | 6/7=3V | | 2-3(y-5)=3+(y+1) | | 4z+6= | | 2t-4s-2t+4s= | | (4b+7)-(6b-3)= | | 12=n-10 | | -x-5y=-54 | | 6x-12=3610x | | f(x)=-0.04x^2+0.8x | | 5(3e+2e-g)= | | 4s+5+5s-5= | | 3m-500=356 | | 2-4x=-7-1x | | 3a+ap=4p | | 3j=-2j+6 | | 2x-xy+y+5=0 | | 9m+8=88 | | -6x+4c-7x=0 | | 4n=10-2 | | -3x-3y=-48 | | 2cos(2x)-sinx=0 | | 2x^2-3x-4(4x+5)= |